The development of biological products based on beneficial microorganisms could extend the range of options for maintaining the health and yield of crops. Rhizobacteria have been used for ‘promoting plant growth. The objectives of this research were to determine the best method of preplant seed treatment through seed conditioning with rhizobacteria which would be effective to improve yields and increase seed quality of hot pepper. This research was conducted in Agronomy Laboratory Haluoleo Unive - Sutariati, Gusti Ayu Kade; Safuan, La Ode (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
The development of biological products based on beneficial microorganisms could extend the range of options for maintaining the health and yield of crops. Rhizobacteria have been used for ‘promoting plant growth. The objectives of this research were to determine the best method of preplant seed treatment through seed conditioning with rhizobacteria which would be effective to improve yields and increase seed quality of hot pepper. This research was conducted in Agronomy Laboratory Haluoleo University and in the field of Wawotobi Seed Farm Centre of Southeast Sulawesi Province. Seed conditioning with rhizobacteria was effective in improving plant growth, yield and seed quality of hot pepper. However, the most effective treatment was the integration of sawdust seed matriconditioning with rhizobacteria Bacillus polymixaBG25. The seed treatment increased fruit total per plant to 51, compared with 26 in the control seeds. The treatment was also effective in increasing seed viability and vigor (germination percentage and vigor index) to 81% and 46% compared with 41% and 26% in the control seeds. Based on this experiment, rhizobacteria B. polymixaBG25 integrated with sawdust seed matriconditioning could be recommended as biofertilizer in improving yield and seed quality of hot pepper. Keywords: hot pepper, matriconditioning, rhizobacteria, sawdust, seed treatment